The referendum in Venezuela: No solution to the political crisis - Susanne Gratius (Stiftung Wissenschaft und Politik (SWP), 2004)
With a majority of 59 percent of the votes, Hugo Chavez was confirmed as the President of Venezuela for the third time since 1998. The opposition, which had pushed through the removal from office referendum after a long legal battle, suffered a clear defeat. However, instead of accepting the result, it now speaks of electoral fraud and provokes new protests. The confrontation between the opposition and the government could therefore continue and paralyze the oil state for an indeterminate period of time. An equally negative scenario would be the further concentration of power in the hands of the charismatic populist and former military Chávez. The most favorable scenario for a solution to the conflict would be the end of the face-off between the political camps, which would, however, require constructive engagement from outside. Such an engagement appears desirable, not least in light of an increasing price of oil. (SWP Comments / SWP)
Keywords: 320